Technical Refinements in Reduction Malarplasty: A CT-Based Evaluation With Clinical Follow-Up - Nguyen D. Huan; Dong H. Trung; Nguyen Van Long; Tuan-Anh Hoang (Journal of Craniofacial Surgery, 2026)
Background: Reduction malarplasty increasingly emphasizes structural preservation and precise facial contouring. This study evaluates CT-based and clinical outcomes following a modified L-shaped osteotomy with standardized technical refinements. Methods: Forty-four consecutive patients underwent reduction malarplasty using a modified L-shaped osteotomy with standardized 6 mm bone strip resection. CT scans were obtained preoperatively and at 6 months postoperatively. Quantitative measurements included malar eminence width (MEW), zygomatic medial displacement (ZMD), zygomatic posterior displacement (ZPD), arch setback at the coronoid level (ASC), malar symmetry index (MSI), and soft-tissue projection (STP). Patient satisfaction was assessed using a 5-point Likert scale. Measurement reliability was evaluated using intraclass correlation coefficients (ICC). Results: MEW decreased significantly from 102.1±3.6 mm to 95.0±3.4 mm, with a mean reduction of 7.1 mm ( P